Cystic hygroma with hydrops fetalis: a rare case report - Kamble, Vidya; Bhatia, Tulsi; Patil, Shaifali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cystic hygromas are malformations of the lymphatics system that appear as fluid-filled, membranous cysts, lined by true epithelium in the anterolateral or occipito-cervical area. They result from the jugular lymphatic obstruction sequence, in which the normal communication between the jugular veins and the jugular lymphatic sacs fail to develop by 40th day of gestation. Most of the cystic hygromas are associated with chromosomal anomalies. When diagnosed in-utero, the survival rate of foetuses affected with cystic hygroma is only 2-6%.When hydrops is present alongwith cystic hygroma, the mortality rate is near 100%. The incidence of cystic hygroma is estimated to be 1 case per 6000-16000 live births. We here present a case of 25 years old primigravida with 16 weeks 5 days of gestation was diagnosed prenatally during ultrasonography for the foetal well-being with a large cystic hygroma with septation extending in the entire length, associated with bilateral pleural effusion and ascites with a variable heart rate. The pregnancy was terminated with the consent of the parents. Foetuses with cystic hygroma are at high risk for adverse outcomes. Due to its extremely poor prognosis, termination should be considered when the diagnosis is made before viability and the chromosomes are abnormal.